COMPREHENSIVE TELEVISION DIGITIZATION DELAY: DECELERATING SUSTAINABLE DEVELOPMENT IN NIGERIA - Nwoga, Chibuzor Cosmas; Obichili, Mercy Ifeyinwa; Taiwo, Ijeoma Njideka (African Journal of Social and Behavioural Sciences, 2022)
The study investigated why digitization of television stations has consistently failed in Nigeria; and its implications on sustainable development. The study anchored on the Diffusion of Innovation and Technological determinism theories adopted survey and focus group discussion research designs. A sample size of 315 was drawn using the Taro Yamane method for survey, while a sample size of 35 was drawn for the focus group discussion through the snowballing sampling technique. Findings showed that digitization will positively affect the broadcast value chain of the media stations but the failure to digitize has negatively affected the sustainable development 9th goal which targets the promotion of infrastructural development, industrialization and innovation in Nigeria. It was recommended among others that the Government should provide sufficient financial resources; and stakeholders comply with the Presidential Advisory Committee directives on Digital Switch Over.